Implikasi Reward dan Punishment untuk Perkembangan Sosial Emosional Anak Usia Dini di TK Hamzanwadi NW Bungtiang: Implications of Rewards and Punishments to Improve Social Emotional Skills of Early Childhood at Hamzanwadi NW Bungtiang Kindergarten, West Sakra District - Husnul Laili (Al-Gafari : Manajemen dan Pendidikan, 2025)
Early childhood education is essentially a form of education that focuses on laying the foundation for growth and development, including motor coordination (fine and gross), emotional intelligence, multiple intelligence and spiritual intelligence in accordance with the uniqueness and growth of early childhood. This study aims to explore the implications of the use of rewards and punishments in improving social-emotional skills in early childhood. In this study, researchers identified several positive implications of the use of appropriate rewards, namely; 1) fair and consistent rewards can increase children's self-esteem. 2) the use of rewards can encourage cooperation and build social skills needed for interaction with peers and adults. 3) appropriate rewards can reinforce desired behaviors, such as sharing, politeness, and emotional control. The type of research used is descriptive qualitative, data obtained by conducting observations, interviews and documentation. The validity of the data uses triangulation techniques. Data analysis was carried out in four stages, namely; data collection, data reduction, data presentation, and drawing conclusions. The results of the study show: 1) Internal and external environmental conditions of Hamzanwadi NW Bungtiang Kindergarten. 2) Teacher strategies in the implications of rewards and punishments in developing children's social emotions at Hamzanwadi NW Bungtiang Kindergarten. 3) Inhibiting factors in implementing rewards and punishments to students at Hamzanwadi NW Bungtiang Kindergarten.